Progress in Mesenchymal Stem Cell Therapy for Ischemic Stroke. (15th June 2021) - Guo, Yinghan; Peng, Yucong; Zeng, Hanhai; Chen, Gao
Abstract : Ischemic stroke (IS) is a serious cerebrovascular disease with high morbidity and disability worldwide. Despite the great efforts that have been made, the prognosis of patients with IS remains unsatisfactory. Notably, recent studies indicated that mesenchymal stem cell (MSCs) therapy is becoming a novel research hotspot with large potential in treating multiple human diseases including IS. The current article is aimed at reviewing the progress of MSC treatment on IS. The mechanism of MSCs in the treatment of IS involved with immune regulation, neuroprotection, angiogenesis, and neural circuit reconstruction. In addition, nutritional cytokines, mitochondria, and extracellular vesicles (EVs) may be the main mediators of the therapeutic effect of MSCs. Transplantation of MSCs-derived EVs (MSCs-EVs) affords a better neuroprotective against IS when compared with transplantation of MSCs alone. MSC therapy can prolong the treatment time window of ischemic stroke, and early administration within 7 days after stroke may be the best treatment opportunity. The deliver routine consists of intraventricular, intravascular, intranasal, and intraperitoneal. Furthermore, several methods such as hypoxic preconditioning and gene technology could increase the homing and survival ability of MSCs after transplantation. In addition, MSCs combined with some drugs or physical therapy measures also show better neurological improvement. These data supported the notion that MSC therapy might be a promising therapeutic strategy for IS. And the application of new technology will promote MSC therapy of IS.